Associations between HbA1c and continuous glucose monitoring‐derived glycaemic variables. Issue 12 (17th July 2019) - Hirsch, I. B.; Welsh, J. B.; Calhoun, P.; Puhr, S.; Walker, T. C.; Price, D. A.
Abstract: Aims: To identify clinically useful associations between HbA1c levels and various continuous glucose monitoring‐derived metrics. Methods: We retrospectively analysed end‐of‐study HbA1c levels and >2 weeks of continuous glucose monitoring data collected from 530 adults with Type 1 diabetes or insulin‐requiring Type 2 diabetes during four randomized trials. Each trial lasted ≥24 weeks and provided central laboratory end‐of‐study HbA1c levels and continuous glucose monitoring data from the preceding 3 months. Participants were assigned to groups based on either HbA1c levels or continuous glucose monitoring‐derived glucose values. Results: HbA1c was strongly correlated with mean glucose value ( r =0.80), time spent with glucose values in the 3.9–10.0 mmol/l range (time in range; r =–0.75) and percentage of glucose values >13.9 mmol/l ( r =0.72), but was weakly correlated with the percentage of glucose values <3.9 mmol/l ( r =–0.39) or <3.0 mmol/l ( r =–0.21). The median percentage of glucose values <3.0 mmol/l was <1.2% (<20 min/day) for all HbA1c ‐based groups, but the median percentage of values >13.9 mmol/l varied from 2.5% (0.6 h/day) to 27.8% (6.7 h/day) in the lowest and highest HbA1c groups, respectively. More than 90% of participants with either <2% of glucose values >13.9 mmol/l, mean glucose <7.8 mmol/l, or time in range >80% had HbA1c levels ≤53 mmol/mol (≤7.0%). For participants with HbA1c ≥64 mmol/mol (≥8.0%), the median time in range was 44%, with 90% of participants having a time in range of <59%. Conclusions: The associations shown in the present study suggest that continuous glucose monitoring‐derived metrics may help guide diabetes therapy intensification efforts in an HbA1c ‐independent manner. What's new?: Glycaemic control can be assessed with HbA1c or with descriptive statistics from continuous glucose monitoring (CGM) data. HbA1c is highly correlated with the average CGM‐derived glucose value. Using HbA1c and CGM data from recently completed clinical trials, we found HbA1c to be highly correlated with the percentage of CGM values indicating hyperglycaemia, but poorly correlated with the percentage of CGM values indicating hypoglycaemia. Because CGM data revealed hypoglycaemia among participants with HbA1c values ≥69 mmol/mol (≥8.5%), relaxation of HbA1c goals is not an effective strategy for hypoglycaemia prevention. CGM‐based heuristics to guide therapy intensification efforts independently of HbA1c are also described.